Analisis Berpikir Logis Siswa SMP Dalam Memecahkan Masalah Matematika Ditinjau Dari Gaya Belajar - Darmono, Prasetyo Budi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to determine how students' logical thinking ability to solve mathematical problems is reviewed from visual learning styles, auditory learning styles and kinesthetic learning styles. This study uses a qualitative research method. This study took research subjects from students of Takhasus Nuril Anwar Maron Middle School in Purworejo Regency. The study took 6 students as research subjects, previously there were 24 students, namely 2 students with visual learning styles, 2 students with auditory learning styles and 2 students with kinesthetic learning styles. The research subjects were selected based on the Learning Style Questionnaire and teacher considerations. Data collection in this study used a learning style questionnaire, tests, field notes, interviews, and documentation. This study used triangulation data analysis techniques. The results of this study indicate that: (1) Students with visual learning styles (V1 and V2) have gone through the stages of classification, connecting, calculating and drawing conclusions properly and correctly. (2) Students with auditory learning styles (A1 and A2) have gone through the stages of classification, connecting, calculating and drawing conclusions properly and correctly. There are differences in the classification and connecting and calculating stages, namely tending not to write down the information obtained in the questions so that sometimes it takes a long time and more often rereading the questions to determine the solution formula and calculating on another paper or through imagination or not written on the answer sheet. (3) Students with a kinesthetic learning style (K1 and K2) have gone through the classification, connecting, calculating and drawing conclusions stages properly and correctly. There are differences in the classification and connecting stages, namely using aids by tending to describe what is known into a picture so that they can easily determine what is being asked and not be wrong. However, in general, logical thinking skills must be honed and applied to facilitate understanding of the material process and solving problems rationally.